Molluscum contagiosum in pediatric patients: to treat or not to treat? Could a personalized imiquimod regimen be the answer to the dilemma?. (2nd January 2022) - Gualdi, Giulio; Pascalucci, Chiara; Panarese, Fabrizio; Prignano, Francesca; Giuliani, Federica; Verga, Emanuele; Amerio, Paolo; Verdolini, Roberto
Abstract: Background: Although molluscum contagiosum virus (MCV) infection is a common disease widespread among children and young adults, there is no shared opinion on treatment that can be divided into physical, chemical, medical (immunomodulating or anti-viral). According to some authors, MCV is best left to clear by itself. Objectives: To assess the clearance of MCV lesions in a sample of pediatric patients. It compares outcomes in treated with Imiquimod cream, compared with non-treated patients. Methods: The sample consits of 48 pediatric patients affected by MVC clinically diagnosed. It was divided into two groups: Group I, treated with Imiquimod 5% cream once/day until the onset of a visible inflammatory reaction. Once the reaction was illicited, application was suspended until the irritation resolved. If the lesion was still present, drug was administered again using the same regimen. The cycle was repeated until complete clinical resolution. Group II, control, comprises non-treated patients. Follow up visits were carried out 12, 16, 20, 48, and 52 weeks from the beginning of treatment. Results: At week 20, all patients except one in the treated group were lesion free. Persistence of MCV lesions was documented in one patient only until week 48. In the control group all patients were still affected by MCV lesions during the follow-up period. Spontaneous clinical resolution of the infection was observed in only 2 patients at week 52. The results of the study show Imiquimod's significant efficacy. Conclusions: Our study is one of the few case-control studies in pediatric population carried out with such long-term follow-up. Efficacy of this personalized treatment, scarce recurrence, absence of cicatricial sequelae and lack of necessity for deep sedation, in the case of children with disseminated lesions, makes the use of Imiquimod the first line of treatment compared with other destructive treatments or with no-treatment at all.